(untitled) (Journal of the Bangladesh Agricultural University, 2026)
Contamination by bacteria is a common complication and serious reason for difficulties in plant tissue culture. The most crucial factor in plant tissue culture technique is the maintenance of aseptic conditions. However, identification and characterization of contaminated bacteria provide information on the sources of contaminants and therefore limit the problem of contamination. In this study five different contaminated vials of plant tissue culture, such as aloe vera (SP1), orchid (SP2), banana (SP3), wheat (SP4), and rice (SP5) were randomly selected and cultured on the nutrient agar media. Five contaminated samples from two individual colonies were isolated and purified by spread and several time streaking techniques. Based on different cultural, morphological, and standard biochemical characteristics, identification and characterization were done. According to Bergey’s Manual of Systematic Bacteriology, the isolates were compared with known organisms and assigned to genera. The all ten isolates were performed to sensitivity tests with three antibiotics. Among ten contaminants isolated from the contaminated plant tissue cultures, most likely four of them were Bacillus spp., four of them were Staphylococcus spp., and two of them were Pseudomonas spp. These findings can support effective contamination management and enhance the success rate of plant tissue culture techniques. J Bangladesh Agril Univ 24(2): 92–100, 2026